Гармонические толщинные колебания неоднородных упругих слоев с искривленными границами - Шульга, Н.А.; Григорьева, Л.О.; Корниенко, В.Ф. (Прикладная механика, 2011)
The thickness vibrations of elastic inhomogeneous bodies of diverse geometry under a dynamical harmonic excitation are studied. The thorough analysis is carried out for a change of amplitude-frequency characteristics of mechanical state of homogeneous and inhomogeneous bodies in dependence of excitation frequency. The frequency spectra are determined for the plane, cylindrical, and spherical layers.